Revitalisasi Industri Rumahan: Pelatihan Kewirausahaan Sosial dan Inovasi Produk Sapu Uyun Berkelanjutan - Sari Sri Handani; Dena Mustika; Yunita Haryani (Universitas Pahlawan Tuanku Tambusai, 2026)
Home industries play an important role in the economic empowerment of rural communities, including in Gunasari Village, Sumedang Regency, West Java. One local potential that has begun to be marginalized is the making of Sapu Uyun, a traditional product made from the uyun plant. Modernization, low interest of the younger generation, and the shift to plastic materials are the main challenges in preserving this tradition. This article aims to describe social entrepreneurship training and innovation of broom products based on natural materials as a revitalization strategy. The implementation method consists of training, mentoring, demonstration plots, consultation, and social engineering. Results show an increase in production and marketing skills, as well as the emergence of sustainable business initiatives. This training not only preserves local culture, but also encourages social and economic transformation of the village.